PELATIHAN DEPLOYMENT DAN IMPLEMENTASI N8N PADA LINGKUNGAN SERVER UNTUK KEBUTUHAN PRODUKSI - Denni Pratama; Raditya Danar Dana; Revan Arrayyan Oktevanio; Muhammad Haidar Hammam (CV. Multi Kreasi Media, 2026)
Community service activities at SMK Kuningan Regency on May 16, 2026, emphasized n8n Deployment and Implementation Training in Server Environments. The objective of the activity was to improve participants' skills in server deployment, automated workflow creation, and error troubleshooting. Participants came from SMK Negeri 1 Kuningan, SMK Negeri 2 Kuningan, and SMK Swasta Harapan Bangsa, with a total of 40. The training method was based on direct practice, discussions, case studies, and mini-projects to ensure effective knowledge transfer and relevance to industry needs. Activities were divided into preparation, theory, practice, evaluation, and mentoring stages. Local and virtual server infrastructure was provided so that participants could immediately carry out deployments. Evaluation was carried out through a participant satisfaction questionnaire, which showed an average score of 4.53 out of 5 and a satisfaction percentage of 90.6%. Aspects of the material, facilitators, methods, and facilities were considered very good. The implementation of the training provided tangible results, such as the creation of workflows for practicum data management, internal application integration, and increased administrative workflow efficiency. The total activity budget of IDR 4,500,000.00 was used for honorariums for experts, training modules, infrastructure, server equipment, consumption, and documentation. This activity bridged the gap between participants' competencies and the needs of the digital industry, while simultaneously increasing the capacity of institutions to support technology-based education. The documentation and training modules served as ongoing reference sources for participants and schools. The results of the activity demonstrated that practical methods and active partner participation are crucial for the success of the service. Intensive mentoring and collaboration between academics and schools supported effective knowledge transfer. Overall, this activity successfully improved participants' technical competencies, facilitated the implementation of workflow automation, and created a positive impact on the vocational education ecosystem in Kuningan Regency.